Efforts To Increase Interest In Early Childhood Reading Through The Use Of Flashcard Media In Harapan Bundaku Districts of Medan Kota - Damaiwaty Ray; Citra Nanda Utami (PG PAUD FIP UNIMED, 2017)
This study aims to increase interest in reading early childhood group B through the use of flashcard media in PAUD Harapan Bundaku Kec. Medan Kota Tahun Ajaran 2012 / 2013.This type of research is PTK (Classroom Action Research) .The result showed that after doing the action on cycle I during two meetings found the result that the average reading interest of children is 56% where, 2 children (8.7%) in very good category, 7 children (30,5%) in good category, 6 children (26%) in enough category, and 8 children (34,8%) in less category. In the second cycle action after the improvement of errors or weaknesses that occurred in cycle I, the average reading interest of children showed an increase up to 91.9% where, 19 children (82.6%) in the category of very good , 4 children (17.4%) in the good category, and no children occupying enough and less categories. Then it can be concluded that